Current issues in research communications: open access and institutional benefit - 2nd report to JISC, July 2010 - Hubbard, Bill; Hodgson, Amanda (Centre for Research Communications, 2010)
This report looks at some of the drivers of interest in open access and the initiatives being taken in response. In particular it addresses the following questions: • Is Green or Gold open access likely to be the more cost effective for HE institutions in the long term? • What can open access offer to libraries struggling with increases in the cost of their subscriptions to academic journals? • How can open access contribute to institutions' preparation for the REF?